We define the operator when applied to two positive integers as shown above. What is the value of ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We claim that ( m + k ) Δ m = 2 k for all k and prove it by induction as follows:
1) When k = 1 ,
( m + 1 ) Δ m = m Δ m + ( m + 1 ) Δ ( m + 1 ) = 1 + 1 = 2 1 .
Therefore, the claim is true for k = 1 .
2) Assuming the claim is true for k , then
( m + k + 1 ) Δ m = ( m + k ) Δ m + ( m + k + 1 ) Δ ( m + 1 ) = 2 k + 2 k = 2 k + 1 .
The claim is also true for k + 1 . Therefore, the claim is true for all k .
Hence, 3 2 Δ 1 1 = ( 1 1 + 2 1 ) Δ 1 1 = 2 2 1 = 2 0 9 7 1 5 2